The cinema of Oliver Stone Art, authorship and activism - Scott , Ian (Manchester University Press, 2019)
This book charts and analyses the work of Oliver Stone - arguably one of the foremost political filmmakers in Hollywood during the last thirty years. Drawing on previously unseen production files from Oliver Stone's personal archives and hours of interviews both with Stone and a range of present and former associates within the industry, the book employs a thematic structure to explore Stone's life and work in terms of war, politics, money, love and corporations. This allows the authors both to provide a synthesis of earlier and later film work as well as locate that work within Stone's developing critique of government. The book explores the development of aesthetic changes in Stone's filmmaking and locates those changes within ongoing academic debates about the relationship between film and history as well as wider debates about Hollywood and the film industry. All of this is explored with detailed reference to the films themselves and related to a set of wider concerns that Stone has sought to grapple with -the American Century, exceptionalism and the American Dream, global empire, government surveillance and corporate accountability. The book concludes with a perspective on Stone's 'brand' as not just an auteur and commercially viable independent filmmaker but as an activist arguing for a very distinct kind of American exceptionalism that seeks a positive role for the US globally whilst eschewing military adventurism.